Prediction of an electrically turbocharged engine and performance prediction in an actual drive cycle - Subramaniam, Kamalleswaran (2022)
The study involves the evaluation of the energy recovery potential of turboshaft separated (decoupled) electric turbocharger and its boosting capability in a sparkignition engine through simulation-based work and comparing it to a conventional turbocharged engine over an actual drive cycle. The main objective of this study is to develop a 1-D numerical model and evaluate the amount of energy that can be recovered over a steady state full-load operating conditions, part-load conditions, and actual, transient drive cycle conditions besides investigating the capabilities of an electric turbocharger. The electric turbocharged system includes two motors and a battery pack to store the recovered electrical energy. GT-Power engine simulation software was used to model both engines and utilizes each of the components described earlier. The conventional turbocharged engine model is first simulated to obtain its performance characteristics. An electric turbocharger is then modelled by separating the turbine from the compressor. The turbine is connected to an electric generator and battery, whereas the compressor is connected to a separate motor. This electrically turbocharged engine was modelled at full load and controlled to produce the same brake power and brake torque characteristics as the similarly sized conventional turbocharged engine. The evaluation of energy recovered from the electrically turbocharged engine from the analysis can assessed in full-load steady state conditions that can be useful for research in part-load and transient studies involving the decoupled electrical turbocharger. At 2500 and 3000 rpm, the energy recovery was 0.57 kW and 0.5 kW respectively at steady state. The maximum electrical energy that was recovered was 5.25 kW at 6500 rpm. Both engines had the same fuel consumption over a drive cycle while no energy recovered for the entire duration of the drive cycle simulation.